Pengaruh Kompetensi Pramuwisata Museum Terhadap Kepuasan Wisatawan Yang Berkunjung di Museum Geologi Bandung - Mulyana, Hadi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
The Bandung Geological Museum has its own charm, especially with a collection of various kinds of fossils and rocks that have complete information, because it will maximise the information obtained if accompanied by a tour guide. This study uses simple regression analysis techniques, the variables used in this study are competencies that are hypothesised to have a positive and significant effect on tourist satisfaction, with descriptive and verification quantitative methods. The sample was 125 respondents with a sample random sample method. The instrument used for data collection is by distributing questionnaires. The results of instrument testing show that all question items are valid above 0.300 and reliable because they are above 0.600. from the research results, descriptively shows that competence is generally good with an average of 3.85 on a scale of 1-5 and tourist satisfaction shows good results with an average of 3.89 on a scale of 1-5, while the results of verification analysis show the coefficient of determination (R2) of 76.10% with fcount 400,221 ftabel 3.94 with a significance of 0.000 <0.005. This also shows that the results of hypothesis testing show that there is a positive and significant influence between the variable competence of tour guides on tourist satisfaction. This shows that variable X simultaneously has a positive and significant influence on variable Y. then the level of influence is 100%.